IMPLEMENTASI MANAJEMEN MUTU TERPADU PENDIDIKAN DI SMP NEGERI 1 PUNGGUR LAMPUNG - Weni Wahidatun Nufusiah (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
This research aims to provide an integrated picture of integrated education quality management at SMP Negeri 1 Punggur, emphasizing customer satisfaction, full participation, measurement, dedication and continuous improvement. Jerome S. Arcaro's hypothesis was applied in this research. A qualitative descriptive approach was used in this research. Through observation, documentation and interviews, data was collected. This research uses a reductionist approach to analyze data, which is then presented as a description and validated with conclusions. The findings of this research show that: 1) Madrasah has succeeded in implementing quality management with a customer-focused approach, thanks to the involvement of external parties in all processes apart from internal parties. Apart from that, this madrasah has excellent accreditation (A) and offers excellent programs. However, the government needs to balance infrastructure and facilities with the number of students enrolled. 2) The existence of MGMP, National Examination coordinators who work under the direction of the school principal, collaboration between teachers and students outside class hours, as well as the existence of main tasks and functions in accordance with their respective job descriptions, all contribute to the success of implementation. Quality management with full involvement. 3) The measurement industry has successfully implemented integrated quality management thanks to an organizational structure that includes control and evaluation meetings.